A Legal review of life insurance policies as a guarantee for obtaining credit from banking institutions (Research study at PT. Allianz Medan) - Mega Ola Silvia; Isnaini Isnaini (Priviet Social Sciences Journal, 2025)
This article aims to determine the significance of problems related to the use of life insurance policies as credit collateral in terms of practice, regulation, and theory. This study focuses on the legal position of life insurance policies as credit collateral and the mechanism and banking use of life insurance policies as credit collateral in banking institutions at PT. Allianz Medan. This study uses Empirical Normative Juridical Legal Research based on interviews as support. In the Indonesian legal system, life insurance policies can be used as collateral to obtain credit lines from such institutions. General provisions on collateral are contained in the Civil Code (KUHPerdata), especially in Book II concerning property and property rights, and in Law Number 40 of 2014 concerning Insurance, which regulates the basic principles, rights, and obligations of the parties in insurance agreements. The mechanism for utilizing life insurance policies as credit collateral in banking institutions studied at PT. Allianz Medan demonstrates a legitimate and structured practice that adheres to national legal provisions, such as the Civil Code, Fiduciary Guarantee Law, and Insurance Law. By transferring the right to receive policy benefits to the bank as collateral, either by replacing the beneficiary or the fiduciary, this practice provides legal certainty for creditors and protection from risk for debtors.